Kinerja Pengarajin Batik Pada Industri Batik Tanjung Bumi melalui Kepemimpinan Tranformasional dan Perencanaan SDM - Mohammad Abbas Sastrodiputro; Samsuki Samsuki (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
The purpose of this study was to determine and analyze the effect of financial literacy, financial inclusion, and financial planning on saving behavior in 2020 batch management students at Trunojoyo Madura University. This research was conducted quantitatively with a research sample of 75 respondents who are 2020 class management students at Trunojoyo Madura University. The sample used by researchers is probability sampling with simple random sampling technique using the slovin formula. The data that has been obtained is then processed using a Partial Least Square-based Structural Model analysis tool (SEM-PLS) with SMART-PLS application. The research results obtained show that financial literacy has a significant positive effect on saving behavior, but the financial inclusion have no significant effect on saving, and financial planning variables have no significant effect on saving behavior in 2020 management students at Trunojoyo Madura University.